An Exploration of the Determinants of the Subjective Well-being of Americans During the Great Recession - Caldera Sánchez, Aida (OECD Publishing, 2014)
This paper uses data from the American Life Panel to understand the determinants of well-being in the United States during the Great Recession. It investigates how various dimensions of subjective wellbeing reflected in the OECD Better Life Framework impact subjective well-being. The results show that income is an important determinant of subjective well-being. The unemployed and the disabled are significantly less satisfied with their lives than the working population, while the retired and the homemakers are more satisfied. The paper expands the existing evidence by showing that homeowners, registered voters and those with access to health insurance have higher levels of subjective well-being. Time spent walking or exercising is positively correlated with happiness, while working more than 50 hours per week or spending time on health-related activities is negatively correlated with subjective well-being, and higher levels of anxiety. This Working Paper relates to the 2014 OECD Economic Survey of United States (www.oecd.org/eco/surveys/economic-survey-united-states.htm)
Keywords: Social Issues/Migration/Health; Economics; United States